Expanding the antimalarial toolkit: Targeting host–parasite interactions - Langhorne, Jean (J Exp Med, 2016)
Recent successes in malaria control are threatened by drug-resistant Plasmodium parasites and insecticide-resistant Anopheles mosquitoes, and first generation vaccines offer only partial protection. New research approaches have highlighted host as well as parasite molecules or pathways that could be targeted for interventions. In this study, we discuss host–parasite interactions at the different stages of the Plasmodium life cycle within the mammalian host and the potential for therapeutics that prevent parasite migration, invasion, intracellular growth, or egress from host cells, as well as parasite-induced pathology.